KOMITMEN STOP STUNTING DALAM KEGIATAN KEMITRAAN DUKUN BERANAK, BIDAN DESA, PAMONG DESA DAN IBU BALITA DI DESA BINAAN FAKULTAS KEDOKTERAN, UNIVERSITAS LAMPUNG - Sutarto Sutarto; Ratna Dewi Puspita Sari; Winda Trijayanthi Utama; Reni Indriyani (Badan Pelaksana Kuliah Kerja Nyata Universitas Lampung, 2022)
Introduction: Stunting is a condition of chronic malnutrition in children. There are many causes of stunting factors, among them the behaviour of pregnant women and child care patterns. Prevention of stunting is very important so it takes commitment together by convergence, taking into account maternal and child health services. With this joint commitment, it will assist maternal and child health services, in the context of preventing stunting in Cipadang village. The purpose of this activity is to establish a partnership relationship and commitment to stunting mothers under five, traditional birth attendants, health cadres and health midwives in the context of STOP Stunting. Method: Executor devotion by method counselling lecture group and continue the discussion. On a different day conducted an Interview depth and delivery of staples needs family. Data analysis using different test statistics in pairs. Results and Discussion: counselling and discussion there is an increase in the knowledge of extension participants in Cipadang village to establish a partnership relationship and commitment to stunting mothers under five, traditional birth attendants, health cadres and health midwives in the context of STOP Stunting through signing the commitment banner of village officials and mothers of children under five